Method for the isolation of circular mitochondrial plasmids from filamentous fungi. - D. Baidyaroy; H. Bertrand (Fungal Genetics Reports, 1997)
Methods for the isolation of highly purified mitochondria (Lambowitz 1979 Meth. Enzymol. 59:421-433) and mitochondrial DNAs (Vierula and Bertrand 1992 Mol. Gen. Genet. 234:361-368) from the filamentous fungi have been available for some time. However, so far, there is no procedure that yields pure plasmid DNAs from mitochondria. We have developed an easy approach for the extraction of circular, mitochondrial plasmids from Neurospora which yields small circular DNAs suited for the analysis of replication intermediates by two-dimensional gel electrophoresis. This method should work well for the extraction of circular mitochondrial plasmids from filamentous fungi in general.